MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA SEKOLAH DASAR PADA MATERI KOLASE DENGAN MEDIA VIDEO - Anwar Munawar (Universitas Pakuan, 2020)
INCREASING ACTIVITY AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS ON LESSONS OF COLLAGE WITH VIDEO MEDIAThis study aims to determine the increase in activity and student learning outcomes, describe the process of increasing student activity and learning outcomes, and measure the magnitude of the increase in activity and learning outcomes in the Collage material using video learning media for Cultural Arts and Crafts in grade IV SD Negeri Lawang Gintung 2, Bogor City. 2019/2020 school year. This research is a Classroom Action Research by providing action on research subjects in two learning cycles. The results of this study indicate that using video media on collage material for learning cultural arts and crafts can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using video media on the learning collage material for Cultural Arts and Crafts, the learning outcomes of students only reached an average value of 68.44 then an increase occurred after using video media to 80.54 in cycle 1 and 98.14 in cycle 2. So it can be concluded that the use of video media in the learning collage material for Cultural Arts and Crafts is very popular with students and there is an increase in student learning outcomes. Therefore, the researcher suggests that the use of video media in the learning collage material for Cultural Arts and Crafts be socialized and used as an alternative in learning Cultural Arts and Crafts in schools.